(untitled) (Islas, 2024)
Introduction: This research identifies the audiovisual cybergenres present in the videos of the YouTube channels of the Escambray and Invasor digital media during the first semester of 2022, while characterizing the pre-production, production, and post-production processes of audiovisual content on both channels. Methods: From a qualitative approach and with qualitative content analysis as a fundamental method, 64 videos from the Escambray and Invasor channels are evaluated. Results: The main findings reveal a limited variety of cybergenres in the media and, notably, an adherence to television typologies at the expense of web-specific formats. Conclusions: Material and human resource constraints contribute to the identified shortcomings in meeting the technical and aesthetic characteristics required for journalistic videos on YouTube.